Gap Junction Intercellular Communication Negatively Regulates Cadmium-Induced Autophagy and Inhibition of Autophagic Flux in Buffalo Rat Liver 3A Cells - Zou, Hui; Yuan, Junzhao; Zhang, Yi; Wang, Tao; Chen, Yan; Yuan, Yan; Bian, Jianchun; Liu, Zongping (Frontiers in Pharmacology, 2020)
Cadmium is an important environmental pollutant, which is a serious threat to human and animal health. A large number of studies have shown that liver is one of the important target organs of cadmium. Stimulation of cells can lead to GJIC and autophagy rapid changes. Previous studies have shown that cadmium can inhibit gap junction intercellular communication (GJIC) and induce autophagy. In order to understand the dynamic changes of GJIC and autophagy in the process of cadmium-induced hepatotoxic injury and the effects of GJIC on autophagy, a time-gradient model of cadmium cytotoxicity was established. The results indicated that within 24 h of cadmium exposure, 5μmol/l cadmium could inhibit GJIC by down regulating the expression levels of Cx43 and disturbing the localization of Cx43 in BRL 3A cells. In addition, cadmium induced autophagy and then inhibited autophagic flux in the later stage. During this process, inhibiting of GJIC could delay the cytotoxic damage of cadmium and induce autophagy, but further blocked autophagic flux, promoting GJIC in order to obtain the opposite results.